Heritage-Lah! A Legacy of a Few Wor(l)ds in Peninsular Malaysia - Pierpaolo De Giosa (Moussons, 2020)
Since the early twentieth century, and particularly since the establishment of the UNESCO World Heritage system, the vocabulary of heritage has expanded tremendously. Today a scientific language of conservation reaches into every corner of the world. Yet, it would be misleading to assume that this heritage idiom is absorbed everywhere in the same way, without local modifications. Focusing on the Malaysian national heritage project, this article explores the interaction between transnational and local terminologies. It first traces the official translation and vernacularization processes involved in the formulation of heritage conservation laws. Beyond the officially sanctioned vocabulary, however, there is a much more variegated heritage word stock that reflects multicultural Malaysian society. This article therefore examines the patrimonial vocabulary as encountered on the ground and alternative discourses to the national heritage project. The ways in which heritage is labelled and described in different contexts shed light on the varied worlds encompassed by the concept of heritage: from the conventional division between tangible and intangible heritage to intimate conceptualisations of familial, ancestral, and communal heritage as well as divergent ways of engaging with colonial legacies.